The Impact of Financial Policy on Banking Stability in Libya - الشلماني, د. سراج عيسى; بوفرنة , د. فاخر مفتاح (Dirasat in Economics and Business, 2021)
The study aimed to measure the impact of financial policy on banking stability in Libya during the period (2008-2019), by dev-eloping a composite index that reflects the stability of the ban-king system, and then studying the effect of financial policy on banking stability, using the Ste-pwise Linear regression model, as well as clarifying the relati-onship between Financial policy indicators and Banking Stability Index. Where the study found that there is one basic variable among the independent variables included in the model that aff-ects the performance of comme-rcial banks in the stability index, and this variable is public reve-nues.